Metacognition ability of grade X students in mathematical problem solving through a digital project-based learning with Edmodo - Misa’adah, Fedriana; Mariani, Scolastika (Unnes Journal of Mathematics Education, 2021)
This study aims to determine how the description of problem-solving abilities supported by metacognition skills in digital learning Project Based Learning assisted by Edmodo. This study used a qualitative method. The population taken in this study were students of class X SMA N 1 Jekulo Kudus. This study used a true experimental design with a pretest-posttest control group design. The sampling technique used in this study was a randomized class technique. Data collection was carried out by means of written tests and interviews. Indicators of problem-solving abilities in this study include (1) identifying problems, (2) planning problems, (3) implementing problem solving in accordance with the plan, and (4) interpreting the results obtained. The results of this study indicate (1) the problem solving abilities of students who have high metacognition abilities meet the four problem solving indicators, (2) the problem solving abilities of students who have moderate metacognitive abilities meet the three problem solving indicators, (3) the problem solving abilities of students who have low metacognition ability only fulfills two problem solving indicators.